Desempenho de bovinos de corte em pastos de Brachiaria brizantha cv. Xaraés manejados em diferentes alturas de pastejo - Alves de Freitas Barbosa, Marco Aurelio; Castro, Leticia Maria; Barbero, Rondineli Pavezzi [UNESP]; Brito, Vinicius Campachi; Miorin, Renan Lucas; Ferreira da Silva, Leandro das Dores; Azambuja Ribeiro, Edson Luis de; Mizubuti, Ivone Yurika (Univ Estadual Londrina, 2013)
The production of grazing cattle has been very interesting, due to the low cost to produce fodder, compared to other sources of forage used to feed these animals, but the adequate management pasture has high influence on the success and profitability of cattle production systems. Thus, the objective of this study was to determine the optimum grazing height of Brachiaria brizantha cv. Xaraes, which provides the highest individual weight gain and gain per area. The stocking rate was continuous, with variable stocking rate. The experimental period was from January to December 2010. Three Nellore males were used in each experimental plot, and, when needed, additional animals were used for adjusting the desired heights. Monthly sampling was obtained to estimate forage mass (kg.ha(-1) of DM) and the structural characteristics of the pastures, such as, leaf: stem ratio. The animals were weighed at the beginning of the experiment and every 28 days, after 12 hours of fasting, to measure the average daily gain (ADG) After weighings were performed adjustments stocking rate to desired heights. Throughout the experimental period the animals received mineral supplementation. The desired sward heights were 15, 30, 45 and 60 cm, with three replicates each. The experimental design was completely randomized with four treatments and three replications. To body weight gain (BWG) and average daily gain (ADG), each animal was considered an experimental unit. To gain per area and stocking rate, the paddock was considered the experimental unit. The leaf: stem ratio showed a linear increasing behavior in the spring and summer seasons. The smaller grazing heights provided higher gain per unit area (812.15 kg ha(-1)), while the highest grazing heights promoted high individual weight gain (0.790 kg.dia(-1)). The results suggest that Xaraes grass pastures should be grazed between 30 and 45 cm to allow reasonable performances by area and individual performances.
Performance of beef cattle on pasture of Brachiaria brizantha cv. Xaraes maintained at different sward heights
Keywords: Average daily gain; Caiua sandstone; chemical composition; Nelore; pasture production; stocking rate